Correlation Between Serum Calcium and National Institute of Health Stroke Score (NIHSS) in Ischemic Stroke Patients (Medical Forum Monthly, 2022)
Objective: To determine correlation between serum Calcium and National Institute of Health Stroke Score (NIHSS) in ischemic stroke patients.Study Design: Descriptive / Cross-sectional studyPlace and Duration of Study: This study was conducted at the Department of Medicine department Fauji foundation Hospital, Rawalpindil from 18th Sep, 2018 to 18th Mar, 2019.Materials and Methods: The study was conducted after the approval of ethical committee. All the patients were educated and an informed consent was taken. All male and female patients of specified age group presenting to OPD/ emergency room & admitted in wards were evaluated. The diagnosis of acute ischemic stroke was based on symptoms of focal neurologic deficit and computed tomography (CT) brain evidence of ischemic infarct. Severity of stroke was assessed using National Institute of Health Stroke Score (NIHSS).Results: Total 150 patients were included according to the inclusion criteria of the study. Mean age (years) in the study was 46.42+18.91 whereas there were 66 (44.0) male and 84 (56.0) female patients who were included in the study. There is a positive correlation (r=0.078) noted between serum calcium and NIHSS score in ischemic stroke patients.Conclusion: There is a positive correlation between serum calcium and National Institute of Health Stroke Score (NIHSS) in ischemic stroke patients. Serum calcium levels may affect the severity of ischaemic injury.